Axotomy-like changes in cat motoneuron electrical properties elicited by botulinum toxin depend on the complete elimination of neuromuscular transmission - Pinter, MJ (J Neurosci, 1991)
The electrical properties of cat medial gastrocnemius (MG) spinal motoneurons were studied 14–21 d following injection of type A botulinum toxin (BTX) into the MG muscle. Treated MG muscles were atrophic, displayed pronounced fibrillation activity, and were markedly but not completely paralyzed. MG motoneuron electrical properties from animals with the highest MG muscle-twitch forces (greater than 20 gm) appeared normal, while motoneuron properties from animals with the lowest MG muscle-twitch forces (less than 10 gm) exhibited axotomy-like changes, though these changes were less pronounced than after axotomy itself. No changes in the axonal conduction velocity were observed, however. Motoneuron connectivity with MG muscle fibers was determined following intracellular stimulation of MG motoneurons by averaging EMG signals from 3 or 4 pairs of recording electrodes inserted into the BTX- treated MG muscles. Normal electrical properties were observed among motoneurons in which detectable EMG activity linked to the intracellular stimulation pulse was observed. The level of this connectivity, however, indicated that a relatively small number of muscle fibers were activated by individual motoneuron action potentials. Axotomy-like changes of electrical properties were observed in MG motoneurons that could not be associated with detectable EMG activity in the BTX-treated MG muscle following repeated trials of intracellular stimulation. These results indicate that the existence of effective neuromuscular transmission at a small number of motor terminals is sufficient to prevent the appearance of axotomy-like changes in motoneuron electrical properties, and that the absence of such transmission at all motor terminals is associated with the appearance of axotomy-like changes. The results suggest that the effects of axotomy itself on motoneuron properties may be based upon the loss or elimination of a potent interaction between muscle and motoneurons normally mediated by neuromuscular transmission.